Analisis Keefektifan Pembelajaran Daring saat Pandemi Covid-19 terhadap Motivasi Belajar Mahasiswa Prodi PKn di Universitas Pendidikan Indonesia - Wibowo, Aggeng Budi; Citra, Anita Permata; Khofsuh, Anita Fatkhiana; Yuniarti, Annisa; Kardiman, Dinda Nur Lathifah; Pratama, Fakhri; Nuha, Firna Kamilatun; Septiani, Istiqomah Putri; Indrawati, Oktri (YASIN, 2022)
The purpose of this study is to see how effective learning is, especially at this time where online learning is based. In addition, this research is also to see whether students experience a decrease in enthusiasm or not when carrying out online learning. And also to see how students can get enthusiasm and motivation in carrying out online learning today. The study used descriptive qualitative methods, using interview, observation and documentation techniques. The research subjects took place on students of the Pancasila and Citizenship Education Study Program at the Indonesian Education University Batch 2020 with 6 students as representatives. Based on the results of research conducted through interviews, it is known that online learning is carried out by utilizing LMS (Learning Management System) facilities and using zoom, google meet, and whatsapp applications as suggestions to help in the learning process. The results also show that during online learning students feel bored and their motivation to learn decreases. The factors that cause learning motivation to decrease are because the implementation of online learning is monotonous, the same learning routine without any changes and the lack of direct interaction between students and lecturers. Students want interactive online learning, namely there is an intense and not monotonous two-way interaction and learning is not only done online but in several meetings it is hoped that it will be done face-to-face.